Особливості тактики використання під час досудового розслідування висновку експерта, в якому реалізовано право на експертну ініціативу - Щербанюк, Д. В.; Scherbanyuk, D. V. (Право і безпека. – 2017. – № 3 (66). – С. 92–97, 2017)
Розглянуто специфіку використання висновку судового експерта, в якому реалізовано право на експертну ініціативу, в доказуванні під час досудового розслідування. Відзначено вплив експертної ініціативи на обрання цілей використання слідчим висновку експерта. Підкреслено суттєве значення висновків експерта, сформульованих ініціативно, для вирішення профілактичних завдань у кримінальному провадженні. Надано рекомендації щодо особливостей використання інформації, одержаної внаслідок експертної ініціативи, для обрання тактичних прийомів проведення окремих слідчих (розшукових) дій та організації тактичних операцій.

The author has studied the specificity of using a forensic expert’s conclusion, which implements the right to an expert initiative while the process of proving during the pre-trial investigation. In particular, the author has emphasized the insufficiency of scientific research of the phenomenon of an expert initiative and its implementation in proving within the criminal proceeding. The general tactical features of using such expert conclusions have been determined. The author has outlined the purposes and directions of their usage, which in general coincide with the purposes and directions of using other evidence, but have a certain specificity. In this regard, it has been emphasized that the expert initiative can not influence the purposes of the examination’s appointment, but it matters with regard to the purposes of using the expert’s conclusion, which can be specified in the direction of narrowing or expansion in comparison with those that were put by the investigator during the appointment of the examination. Significance of the expert’s conclusions initially formulated to identify the causes and conditions that contributed to the commission of a crime and, accordingly, to solve preventive tasks within the criminal proceedings. The author has provided recommendations on the peculiarities of the influence of information obtained by the investigator as a result of the expert initiative on the selection of tactical methods of carrying out certain investigative (search) actions by the example of interrogation tactics. The author has also determined the peculiarities of the influence of the initiative on the organization of tactical operations during the pre-trial investigation realized in the expert’s conclusion.

Рассмотрена специфика использования заключения судебного эксперта, в котором реализовано право на экспертную инициативу, в доказывании в ходе досудебного расследования. Отмечено влияние экспертной инициативы на выбор целей использования следователем заключения эксперта. Подчёркнуто значение выводов эксперта, сформулированных инициативно, для решения профилактических задач в уголовном производстве. Приведены рекомендации по особенностям использования информации, полученной в результате экспертной инициативы, для выбора тактических приёмов проведения отдельных следственных (розыскных) действий и организации тактических операций.
Features of the tactics of using an expert’s conclusion during the pre-trial investigation, which implements the right to an expert initiative
Особенности тактики использования в досудебном расследовании заключения эксперта, в котором реализовано право на экспертную инициативу
Щербанюк, Д. В. Особливості тактики використання під час досудового розслідування висновку експерта, в якому реалізовано право на експертну ініціативу / Д. В. Щербанюк // Право і безпека. – 2017. – № 3 (66). – С. 92–97.
Scherbanyuk, D.V. (2017), “Features of the tactics of using an expert’s conclusion during the pre-trial investigation, which implements the right to an expert initiative” [“Osoblyvosti taktyky vykorystannia pid chas dosudovoho rozsliduvannia vysnovku eksperta, v yakomu realizovano pravo na ekspertnu initsiatyvu”], Pravo i Bezpeka, No. 3, pp. 92–97.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Криміналістика. Criminalistics. Криминалистика; судова експертиза; криміналістична тактика; судовий експерт; кримінальне провадження; досудове розслідування; експертна ініціатива; forensic examination; forensic tactics; court expert; criminal proceedings; pre-trial investigation; expert initiative; судебная экспертиза; криминалистическая тактика; судебный эксперт; уголовное производство; досудебное расследование; экспертная инициатива